Serum bilirubin concentration in breast-fed newborn babies at Larantuka General Hospital, East Flores - Tri Yasa P.; Abdul Hamid S. (Indonesian Pediatric Society, 2001)
Neonatal hyperbilirubinemia is a common problem not only to pediatricians but also to the parents. Breastfeeding is known as one of the factors associated with hyperbilirubinemia. The aim of the study was to determine serum bilirubin concentration and factors related to hyperbilirubinemia in breast-fed newborn babies. A cross sectional study was done on 45 well babies born at Larantuka General Hospital, East Flores, from August to October 1998. Data including personal data, frequency of breast-feeding, frequency of urination, meconium passage, and weight loss, were collected through questionnaires, presented in tables, and analyzed using chi-square test. The prevalence of hyperbilirubinemia in breast-fed babies was 13%. It was correlated significantly with the frequency of breast-feeding (p<0.01), meconium passage (p<0.02), sufficiency of breast milk (p<0.05), and weight loss (p<0.05). The significant risk factors for neonatal hyperbilirubinemia were the frequency of breast-feeding, meconium passage, sufficiency of breast milk, and weight loss. Immediate and frequent breast-feeding is recommended for the management of neonatal hyperbilirubinemia.